Implementasi Pembelajaran Daring Pada Masa Pandemi Corona Virus Disease 19 (COVID-19) - Tri Agung Prasetio (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This study aims to determine the implementation of online learning during the coronavirusdisease 19 (Covid-19) pandemic which was carried out at SD Negeri Paremono 1 Mungkid.The subjects of this study were selected by purposive sampling. Data collection techniqueswere carried out by observation, interviews, and documentation. research informants areteachers, students, parents. Test the validity of the data using triangulation of sources,times, and methods. The data analysis used is the Miles and Huberman model, namelydata reduction, data presentation and data conclusion/verification.The results of the study can be concluded that (1) The implementation of online learningby teachers uses 2 learning systems, namely online and home visits. teachers usetechnology as online learning media such as whatsapp, youtube and google form (2)Supporting and inhibiting factors for the implementation of online learning are: a)supporting factors, namely support for infrastructure such as cellphones, laptops, andinternet quotas and stable networks in schools. Good mood of students in participating inonline learning, as well as guidance and assistance of parents in student learning. b) Theinhibiting factor is the limited time in the delivery of learning material so that the materialis not delivered optimally. Some students experience internet network problems so thatthey are not on time in participating in learning. Students who feel bored in participatingin online learning so that students are even engrossed in playing games on theircellphones. The inhibiting factor experienced by parents is time and lack of understandingof Information Technology (IT) so that it is difficult to guide students.